A Study on the Pattern of Traumatic Faciomaxillary Fractures and Their Management - Dr. Monjita Borthakur; Dr. Smrity Rupa Borah Dutta (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
The most frequent life-threatening emergency in both industrialized and developing countries is a faciomaxillary injury, which accounts for 7.4–8.7% of emergency medical care. These injuries not only cause functional derangement but also cause face disfigurement, which can result in psychological stress. Aim: To study the pattern of faciomaxillary fractures and their management in trauma cases. Methodology: The study was conducted on 120 patients with traumatic Faciomaxillary fracture over a one-year period. Data regarding patient particulars, cause, site of fracture, and management were recorded, and statistical analysis was done. Results: Out of the 120 patients, the commonest fracture was found to be nasal bone (33%), with male preponderance (82%) in the age group of young adults (63%). Most common cause found was RTA (51%). Open reduction was done for fracture mandible and middle third of face. Discussion: Demographic distribution, cause, management and complications of faciomaxillary fractures were compared to previous studies. Nasal bone has been found to be most commonly affected. 35% of patients needed open reduction. Conclusion: The authorities should be made aware of the need to enforce strict traffic laws due to the rising number of traffic accidents.